(untitled) (Vietnam Journal of Community Medicine, 2021)
A descriptive cross-sectional study on 424 students to assess the status of oral diseases of students at two secondary schools Ky Ba and Phu Xuan, Thai Binh city. The research results show that: The overall prevalence of dental disease (BRM) of the two schools is 53.8% (Phu Xuan: 70.9%; Ky Ba 41.8%, p<0.05): Cavities teeth (33.5%); Cavities lost fillings - teeth (SMT-R) (38.0%); Gingivitis (11.1%); tartar (11.6%); dental plaque (22.6%); BRM prevalence was higher in women than in men (female: 56.1%; male: 43.9%; p<0.05). Dental caries: The rate of malaria in Phu Xuan school was higher than in Ky Ba school (44.6%; 25.7% and p<0.05). Female students have a higher risk of malaria than male students (OR = 2.35; 95% CI: 1.55-3.56). Good OHI-S index reached 72.6%. The index of periodontal disease: GI, CI-S and DI-S of Phu Xuan school all have a higher risk than the upper periodontal index of Ky Ba school (OR = 10.24; 95%, respectively). CI: 4.47-23.5), (OR = 4.19; 95% CI: 2.18-8.07) and (OR = 4.42; 95% CI: 2.71-7.21) .